Informality and work status - Gary S. Fields (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The most important determinant of households' livelihoods is how much they earn for their labour. People in informal work are more likely to be low earners, to live in poverty, and to make fewer transitions into the higher-paying work statuses. The paper is divided into three main sections: what we mean by informality and work status, why we should differentiate between work statuses, and what we can learn by analysing work statuses and transitions between them.
Keywords: J3; J6; O1; O2; 330; informal work; work status; livelihoods; poverty; transitions